Anais Do XXVIII Simpósio Brasileiro De Informática Na Educação (SBIE 2017) 2017
DOI: 10.5753/cbie.sbie.2017.987
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality as an Assistive Technology to Support the Cognitive Development of People With Intellectual and Multiple Disabilities

Abstract: Abstract. This study investigated the efficacy of a virtual reality-based cognitive and motor coordination training for people with intellectual and multiple disabilities, focusing on community participation. Ten people with disabilities were selected from an institutional care for people with disabilities and they were enrolled in a five-week experiment, which consisted in shopping in a virtual reality supermarket. The results show that the patients demonstrated statistically significant improvements regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This versatility allows RACHs to select a type of VR that will best suit their setting while meeting the individual needs of their residents. For these reasons, the authors agree with D 'Cunha et al (2019) and da Cunha and da Silva (2017) that VR can be categorised as assistive technology (AT), as it can be used to facilitate opportunities of meaningful engagement for older adults living with dementia. Westphal (2017) explains for intervention to be effective for older adults living with dementia it should be familiar yet novel, simple yet intuitive, and tailored to the individual's pace, engaging multiple senses while encouraging individualised physical activity; VR meets these criteria.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…This versatility allows RACHs to select a type of VR that will best suit their setting while meeting the individual needs of their residents. For these reasons, the authors agree with D 'Cunha et al (2019) and da Cunha and da Silva (2017) that VR can be categorised as assistive technology (AT), as it can be used to facilitate opportunities of meaningful engagement for older adults living with dementia. Westphal (2017) explains for intervention to be effective for older adults living with dementia it should be familiar yet novel, simple yet intuitive, and tailored to the individual's pace, engaging multiple senses while encouraging individualised physical activity; VR meets these criteria.…”
Section: Introductionmentioning
confidence: 61%
“…This versatility allows RACHs to select a type of VR that will best suit their setting while meeting the individual needs of their residents. For these reasons, the authors agree with D'Cunha et al (2019) and da Cunha and da Silva (2017) that VR can be categorised as assistive technology (AT), as it can be used to facilitate opportunities of meaningful engagement for older adults living with dementia.…”
Section: Introductionmentioning
confidence: 76%
“…Regarding the use of the virtual reality technology and the VR-DAD system itself, there was no need to apply a perform training phase, because the selected participants for the case study presented in this work had already participated in another virtual reality study using a similar system, a couple of months ago, which is discussed in study [22]. Nevertheless, as the VR-based task presented in this work is totally different from the previous one, an use demonstration was provided by one of the authors of this work.…”
Section: System Use Demonstrationmentioning
confidence: 99%
“…A virtual world, aimed at teaching children with Down syndrome to read a clock, has achieved its educational goals, as children appreciated the virtual environment and actively explored it with very few difficulties (Ripamonti & Maggiorini, 2011). Research has shown that children with CDs can benefit from the use of touchscreen displays (Ko, Sung, & Joeng, 2017), while similar studies report positive findings regarding the improvement of life-readiness skills (including daily tasks) of students with CDs (Cunha & da Silva, 2017;Dunn, Barrio, & Hsiao, 2016) when ICT technology is used.…”
Section: Related Workmentioning
confidence: 99%